Mandibular reconstructions with free fibula flap using standardized partially adjustable cutting guides or CAD/CAM technique: a three- and two-dimensional comparison - Weitz, Jochen; Grabenhorst, Alex; Singer, Hannes; Niu, Minli; Grill, Florian D.; Kamreh, Daniel; Claßen, Carolina A. S.; Wolff, Klaus-Dietrich; Ritschl, Lucas M. (Frontiers in Oncology, 2023)
Background Mandibular reconstruction with the fibula free flap (FFF) is performed freehand, CAD/CAM-assisted, or by using partially adjustable resection/reconstruction aids. The two latter options represent the contemporary reconstructive solutions of the recent decade. The purpose of this study was to compare both auxiliary techniques with regard to feasibility, accuracy, and operative parameters. Methods and materials The first twenty consecutively operated patients requiring a mandibular reconstruction (within angle-to-angle) with the FFF using the partially adjustable resection aids between January 2017 and December 2019 at our department were included. Additionally, matching CAD/CAM FFF cases were used as control group in this cross-sectional study. Medical records and general information (sex, age, indication for surgery, extent of resection, number of segments, duration of surgery, and ischemia time) were analyzed. In addition, the pre- and postoperative Digital Imaging and Communications in Medicine data of the mandibles were converted to standard tessellation language (.stl) files. Conventional measurements – six horizontal distances (A–F) and temporo-mandibular joint (TMJ) spaces – and the root mean square error (RMSE) for three-dimensional analysis were measured and calculated. Results In total, 40 patients were enrolled (20:20). Overall operation time, ischemia time, and the interval between ischemia time start until end of operation showed no significant differences. No significant difference between the two groups were revealed in conventional measurements of distances (A–D) and TMJ spaces. The ∆ differences for the distance F (between the mandibular foramina) and the right medial joint space were significantly lower in the ReconGuide group. The RMSE analysis of the two groups showed no significant difference (p=0.925), with an overall median RMSE of 3.1 mm (2.2–3.7) in the CAD/CAM and 2.9 mm (2.2–3.8) in the ReconGuide groups. Conclusions The reconstructive surgeon can achieve comparable postoperative results regardless of technique, which may favor the ReconGuide use in mandibular angle-to-angle reconstruction over the CAD/CAM technique because of less preoperative planning time and lower costs per case.